Unit commitment problem solved with adaptive particle swarm optimization - Muthu, Ramesh Babu; Chandrasekaran, Venkatesh Kumar; Munusamy, Bharathraj; Sankaranarayanan, Dashagireevan (Institute of Advanced Engineering and Science, 2025)
This article presents an innovative approach that solves the problem of generation scheduling by supplying all possible operating states for generating units for the given time schedule over the day. The scheduling variables are set up to code the load demand as an integer each day. The proposed adaptive particle swarm optimization (APSO) technique is used to solve the generation scheduling issue by a method of optimization considering production as well as transitory costs. The system and generator constraints are considered when solving the problem, which includes minimum and maximum uptime and downtime as well as the amount of energy produced by each producing unit (like capacity reserves). This paper describes the suggested algorithm that can be applied for unit commitment problems with wind and heat units. Test systems with 26 and 10 units are used to validate the suggested algorithm.